The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fphar.2022.839640
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Prevents Lipid Accumulation, Mitochondrial Dysfunction, and Gut Microbiota Dysbiosis in Mice With Diabetic Cardiovascular Disease

Abstract: Type 2 diabetes mellitus (T2DM) is associated with cardiovascular disease (CVD) and sodium glucose cotransporter 2 inhibitors, as oral medications for T2DM treatment have shown the potential to improve vascular dysfunction. The aim of this study was to evaluate the ability of canagliflozin (Cana) to relieve CVD in T2DM mice and its possible action mechanism. Mice with diabetic CVD was conducted by a high-fat diet for 24 weeks, followed by oral gavaging with metformin (200 mg/kg/day) or Cana (50 mg/kg/day) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 89 publications
(93 reference statements)
1
14
0
Order By: Relevance
“…Canagliflozin (Cana), a hypoglycemic drug of sodium-glucose cotransporter 2 inhibitor (SGLT2i), has shown promising anticardiovascular effect in multicenter clinical randomized doubleblind studies, which can reduce the risk of cardiovascular death or hospitalization for heart failure in diabetic patients and nondiabetic patients (10,11). Meanwhile, Cana have shown the ability to attenuate oxidative stress and improve myocardial function by suppressing apoptosis, promoting antioxidant and antiinflammatory pathways (11,12). At present, the protective effects of Cana on the heart have been gradually revealed in various myocardial injuries, such as autoimmune myocarditis (13), myocardial lipotoxicity (12) and even isoprenaline-induced cardiotoxicity (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canagliflozin (Cana), a hypoglycemic drug of sodium-glucose cotransporter 2 inhibitor (SGLT2i), has shown promising anticardiovascular effect in multicenter clinical randomized doubleblind studies, which can reduce the risk of cardiovascular death or hospitalization for heart failure in diabetic patients and nondiabetic patients (10,11). Meanwhile, Cana have shown the ability to attenuate oxidative stress and improve myocardial function by suppressing apoptosis, promoting antioxidant and antiinflammatory pathways (11,12). At present, the protective effects of Cana on the heart have been gradually revealed in various myocardial injuries, such as autoimmune myocarditis (13), myocardial lipotoxicity (12) and even isoprenaline-induced cardiotoxicity (14).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Cana have shown the ability to attenuate oxidative stress and improve myocardial function by suppressing apoptosis, promoting antioxidant and antiinflammatory pathways (11,12). At present, the protective effects of Cana on the heart have been gradually revealed in various myocardial injuries, such as autoimmune myocarditis (13), myocardial lipotoxicity (12) and even isoprenaline-induced cardiotoxicity (14). In addition, a recent study reported that Cana may exert its cardiovascular benefits partly via its mitigation of ferroptosis (15), which is similar to the effect of empagliflozin ( 16), another SGLT2i.…”
Section: Introductionmentioning
confidence: 99%
“…Dapagliflozin, empagliflozin, and canagliflozin revealed favorable effects on microbiota with tight interactions with T2DM, metabolic syndrome, and CVD in studies on mice [ 55 , 56 , 57 , 58 ]. Researchers used different rat categories, from diet-induced mice to subjects with nephropathy, and this heterogeneity overburdened the challenge of analyzing the impact of SGLT-2i on the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Standardization is another important aspect that has to be considered, as the participants’ characteristics can also induce different baseline microbiota distributions. The differences between interspecies in terms of gut microbiota should not be overlooked, acknowledging the fact that the data from the studies on mice microbiota cannot be extrapolated to human subjects [ 56 , 57 , 58 , 59 ]. We have to consider the interracial differences in terms of the gut microbial architecture, because patients from different geographical areas may have different microbial signatures, partly because of genetic factors but also due to external factors, such as cultural patterns (different diet) or various environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Partial tissues were fixed in 4% paraformaldehyde solution immediately. After dehydration and embedding, tissues were cut into 4-μm-thick sections and analyzed by H&E or Oil Red O ( Wang et al, 2021 ; Wang et al, 2022 ). Quantity was analyzed using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%